Effects of Social Support and Personal Factors on Educational Aspirations of Students Class XI Madrasah Aliyah in West Halmahera, North Maluku Province - Amanan Saumur (Didaktika Religia, 2019)
There is not much Islamic madrasa in the majority of non-Muslim regions. The existence of Islamic madrassas is important for Muslim communities who live in predominantly non-Muslim areas. In the province of North Maluku, there are approximately nine madrassas that have existed until now. Therefore, researchers are interested in examining the existence of these madrassas in a society that is predominantly non-Muslim. The research focuses on is the social support influence the aspiration of the students of Madrasah Aliyah in West Halmahera regency. The method used in this research is quantitative correlational which aim to know the correlation between the predictor variable with the criterium variable. The result of the research shows that for all, education aspiration, social support, and also perception and subject its in-between position category. Subject shows that aspiration education has a correlation with social support and perception. Social support research subject has more than a contribution to education aspiration compare with perception, that’s why, its concluded that simultaneity social support and perception have the influence to education aspiration, The highly social support, the high education aspiration. Otherwise, the high education perception owned, it means the high aspiration education must be owned too.